PROTON ADSORPTION AT AN ADULARIA FELDSPAR SURFACE - Stillings L.L.; Brantley S.L.; Machesky M.L. (My University, 1995)
The concentration of H+ which reacts with an adularia surface, [H+s], was measured with acid-base titrations of adularia powder-water suspensions. Due to the complexity of feldspar surface reactions, it was necessary to calculate a H+ mass balance in order to separate the fractions of H+ involved in cation exchange reactions, [H+ex]; dissolution reactions, [H+dis]; and adsorption at surface hydroxyl sites, [H+ads]. Reproducibility of acid and base titrations of H+s was pH-dependent, ranging from +/-3 μmol H+ m-2 at pH 4 to +/-1.5 μmol H+ m-2 at pH > 6.5. This departure was due to the exchange of K+fsp for H+aq, which was not completely reversible under the conditions of our experiment. Reproducibility of acid and base titration curves for [H+ads] vs. pH was +/-1.5 μmol m-2, suggesting the H+ adsorption reaction was reversible.Fifteen μmol H+ m-2 reacted with the washed feldspar surface during an acid titration from pH 10 to pH 4, in distilled water. 50-60% of the total is attributed to cation exchange, which is estimated to take place at >3 a depth within the surface, suggesting the near-surface is porous, and that H+ reacts with sites within the surface pores as well as at the external surface. Less than 5% of [H+s] was due to [H+dis], and the remainder to [H+ads]. [H+ex] decreases with increasing concentrations of NaCl, presumably because of competition between the solution ions, H+ and Na+, for K+ exchange sites in the feldspar. [H+ex] is independent of (CH3)4NCl concentrations, suggesting that (CH3)4N+ cannot compete with H+ for the K+ exchange sites. The relatively large diameter of (CH3)4N+ probably prohibits it from penetrating the pores of the adularia surface; therefore, it cannot access exchange sites within the pores which are available to the smaller H+, Na+, and K+ ions.Feldspar dissolution rates, often modeled as rate = kH[H+ads]n, wherekH = the rate constant, and n = the reaction order, have been observed to decrease with increasing ionic strength. Because we observe an ionic strength dependence in [H+ex], rather than [H+ads], we suggest a rate model where rate =kH [H+ex]n. This expression emphasizes that dissolution rates are dependent upon K+-H+ exchange at the feldspar surface, and that rates decrease with increasing {Na+} due to competition between Na+ and H+ for the surface exchange site.